2008
DOI: 10.1080/09286580701772029
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Content for a New Quality of Life Questionnaire for Students with Low Vision (The Impact of Vision Impairment on Children: IVI_C)

Abstract: The multi-perspective development strategy for a new questionnaire has established that it is crucial to integrate different stakeholders' perspectives. By doing so, it will be possible to develop a balanced questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 25 publications
3
49
0
1
Order By: Relevance
“…9,27,62,84 For example, the 25-item Cardiff Visual Ability Questionnaire for Children (CVAQC) assesses self-reported visual ability in children and young people with a visual impairment. 84 One important function of outcomes research is to assess the cost effectiveness of health and social care interventions so that policy makers can make judgments about a particular treatment/intervention.…”
Section: Outcome Measures For Assessing the Effectiveness Of A Sermentioning
confidence: 99%
See 1 more Smart Citation
“…9,27,62,84 For example, the 25-item Cardiff Visual Ability Questionnaire for Children (CVAQC) assesses self-reported visual ability in children and young people with a visual impairment. 84 One important function of outcomes research is to assess the cost effectiveness of health and social care interventions so that policy makers can make judgments about a particular treatment/intervention.…”
Section: Outcome Measures For Assessing the Effectiveness Of A Sermentioning
confidence: 99%
“…Most QoL questionnaires for children have been developed from, or include, opinions and experience of caregivers and/or experts rather than from the direct responses of children. 8,27,62 More recently, focus group work with children and Rasch analysis have been used to develop an outcome measure of direct relevance to the lives of children but it has not yet been used to evaluate service provision. 84 There are other practical barriers which hinder the assessment of vision rehabilitation in children, including the relatively low prevalence of visual impairment in this age group 113 and the numerous causes of visual impairment in children, which often form part of wider conditions or disabilities, making this a difficult group to research.…”
Section: J the Effect Of Rehabilitation On Outcomes In Childrenmentioning
confidence: 99%
“…Although it only concerns children from 8 to 18 years old with different causes of impaired vision (albinism, congenital conditions, or juvenile-onset degenerative conditions) and it does not address treatment options, it does underline the major differences between families and professionnals about a patient's needs and concerns. 7,8 Wen et al 34 also showed that preschool children with strabismus had a significantly worse QOL than unaffected children, confirming what was long suspected.…”
Section: Ophthalmological Assessmentmentioning
confidence: 70%
“…27 While early assessment and appropriate correction of vision impairment are essential, it is also important to understand how impaired vision affects a patient's dayto-day activities such as dressing, eating, writing, communications or interactions with others, travel, mood, and social relationships. In 2008 Cochrane et al 7 first identified the different aspects that needed to be addressed to develop a complete questionnaire to evaluate the impact of vision impairment in children (ages 8-18 years), based on information from vision-impaired children and their support providers. These authors interviewed visually impaired children and their families, teachers, and special instructors to include all perspectives.…”
Section: Ophthalmological Assessmentmentioning
confidence: 99%
“…Moreover, none of the tools reflect the opinions and experiences of the population of concern -the focus groups -and instead rely upon the opinion of experts or caregivers (Balch & Mertens, 1999;Ronen et al, 2001). Proxy opinion is recognised as a serious limitation to accurate interpretation of quality of life (Fayers & Machin, 2000;Cochrane et al, 2008). Therefore, there is a need for a user-defined tool (Ronen et al, 2001) to describe and quantify the impact of hearing loss on children.…”
Section: Introductionmentioning
confidence: 99%